'Deadlier than Boko Haram': Representations of the Nigerian herder–farmer conflict in the local and foreign press. (March 2022) - Chiluwa, Innocent; Chiluwa, Isioma M
This corpus-based discourse study briefly reviews the activities of Boko Haram and the conflict between the nomadic herdsmen and sedentary agrarian farmers of north-central and southern Nigeria. But the study focuses on the representations of the main actors in the conflict and the conflict itself in the Western media and the Nigerian press, and examines the ideological implications of these representations as well as the possible consequences of some particular evaluations of the conflicts for peace and security in Nigeria. The article's findings show that the constructions of the conflict and the main actors in the Nigerian press are highly sensational, divisive and dangerous. While the foreign press appears much more objective and often constructs the conflict as 'deadlier than Boko Haram', the reports still appear to minimize the seriousness of the conflict and construct the actions of the main actors from a perspective that would appeal only to foreign audiences.